2022
DOI: 10.1021/jacsau.2c00413
|View full text |Cite
|
Sign up to set email alerts
|

From N–H Nitration to Controllable Aromatic Mononitration and Dinitration─The Discovery of a Versatile and Powerful N-Nitropyrazole Nitrating Reagent

Abstract: Nitroaromatics are tremendously valuable organic compounds with a long history of being used as pharmaceuticals, agrochemicals, and explosives as well as vital intermediates to a wide variety of chemicals. Consequently, the exploration of aromatic nitration has become an important endeavor in both academia and industry. Herein, we report the identification of a powerful nitrating reagent, 5-methyl-1,3-dinitro-1 H -pyrazole, from the N -nitro-type reagent library co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…[9] Very recently, Zhuang and co-workers reported N-nitropyrazoles as versatile nitrating reagents that efficiently introduce nitro groups in (hetero)arenes, including protected anilines, under heat conditions. [10] Despite the abovementioned progress, nitration protocols that proceed under room temperature and work for a variety of anilines without the use of transition metals or acids are still highly desired. Recently, we reported that 5-methyl-dinitroimidazole (DNIm) is a photoreactive reagent that converts phenol derivatives to corresponding ortho-nitrophenol products under 390 nm light irradiation in aqueous solutions.…”
Section: Background and Originality Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Very recently, Zhuang and co-workers reported N-nitropyrazoles as versatile nitrating reagents that efficiently introduce nitro groups in (hetero)arenes, including protected anilines, under heat conditions. [10] Despite the abovementioned progress, nitration protocols that proceed under room temperature and work for a variety of anilines without the use of transition metals or acids are still highly desired. Recently, we reported that 5-methyl-dinitroimidazole (DNIm) is a photoreactive reagent that converts phenol derivatives to corresponding ortho-nitrophenol products under 390 nm light irradiation in aqueous solutions.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 9 ] Very recently, Zhuang and co‐workers reported N ‐nitropyrazoles as versatile nitrating reagents that efficiently introduce nitro groups in (hetero)arenes, including protected anilines, under heat conditions. [ 10 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…13 Zhuang, Zhou, Shi, and coworkers succeeded in the development of 10 as a facile Nnitropyrazole reagent for controllable aromatic mononitration and dinitration. 21 The advantages of N-nitro-type reagents include mild reaction conditions, good functional group tolerance, and arene substrates without the requirement of being prefunctionalized. It is noteworthy that the nitration capability is closely related to the host-structure of the N-nitro type reagent.…”
mentioning
confidence: 99%
“…9 had been developed as a light-controlled nitration reagent of proteins by Wang, Tian, and co-workers . Zhuang, Zhou, Shi, and co-workers succeeded in the development of 10 as a facile N -nitropyrazole reagent for controllable aromatic mononitration and dinitration . The advantages of N -nitro-type reagents include mild reaction conditions, good functional group tolerance, and arene substrates without the requirement of being prefunctionalized.…”
mentioning
confidence: 99%
“…This method demonstrated exceptional functional group tolerance and was used for the late-stage functionalization of complex molecules. In 2022, Zhuang and co-workers reported a controllable aromatic mononitration and dinitration method with N -nitropyrazole as the nitrating reagent and Lewis acid as the catalyst (Scheme c) …”
mentioning
confidence: 99%